Analysis of Visionary Leadership on Teacher Innovativeness In A Review at The High School Level (SMA) - Noviyanti, Rani (International Humanity Advance, Business & Sciences, 2025)
Visionary leadership plays a crucial role in fostering teacher innovativeness, especially in Senior High Schools (SMA). This study analyzes the influence of visionary leadership on teachers' ability to innovate in their teaching methods. Visionary school principals are characterized by their ability to articulate a clear vision, inspire their staff, and create an environment conducive to creativity and professional growth. The results show that teachers under visionary leadership demonstrate higher motivation to utilize educational technologies, adopt project-based learning strategies, and implement innovative assessment methods. However, several challenges remain, including resistance to change, limited resources, and administrative workloads. Addressing these barriers requires strategic initiatives, such as professional training, reducing non-teaching tasks for teachers, and fostering collaborative practices among educators. The findings highlight a positive correlation between visionary leadership and teacher innovativeness, emphasizing the importance of supportive leadership in adapting to educational advancements and improving teaching quality. This study underscores the necessity for educational stakeholders to promote visionary leadership as a means to achieve adaptive, innovative, and high-quality education in Senior High Schools.